The Functional Deubiquitinating Enzymes in Control of Innate Antiviral Immunity. Issue 2 (15th December 2020) - Zong, Zhi; Zhang, Zhengkui; Wu, Liming; Zhang, Long; Zhou, Fangfang
Abstract: Innate antiviral immunity is the first line of host defense against invading viral pathogens. Immunity activation primarily relies on the recognition of pathogen‐associated molecular patterns (PAMPs) by pattern recognition receptors (PRRs). Viral proteins or nucleic acids mainly engage three classes of PRRs: Toll‐like receptors (TLRs), retinoic acid‐inducible gene I (RIG‐I)‐like receptors (RLRs), and DNA sensor cyclic GMP‐AMP (cGAMP) synthase (cGAS). These receptors initiate a series of signaling cascades that lead to the production of proinflammatory cytokines and type I interferon (IFN‐I) in response to viral infection. This system requires precise regulation to avoid aberrant activation. Emerging evidence has unveiled the crucial roles that the ubiquitin system, especially deubiquitinating enzymes (DUBs), play in controlling immune responses. In this review, an overview of the most current findings on the function of DUBs in the innate antiviral immune pathways is provided. Insights into the role of viral DUBs in counteracting host immune responses are also provided. Furthermore, the prospects and challenges of utilizing DUBs as therapeutic targets for infectious diseases are discussed. Abstract : This review systematically summarizes the role and mechanisms of deubiquitinating enzymes (DUBs) in regulating innate antiviral signaling via the Toll‐like receptors (TLRs), RIG‐I like receptors (RLRs), and cyclic GMP‐AMP synthase (cGAS). The role of viral DUBs counteracting host immune responses is also concluded. Moreover, the prospects and challenges of utilizing DUBs as therapeutic targets for treatment of infectious diseases like COVID‐19 are also discussed.